EVALUASI KINERJA JARINGAN IRIGASI DAERAH IRIGASI BARO KANAN KABUPATEN PIDIE - Husaini Husaini; Eldiana Fatimah; Masimin Masimin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Baro Kanan Irrigation Area is one of the irrigation areas which is focused on increasing the productivity food crop in Pidie District. The Baro Kanan serves to irrigate of agricultural land of 8,920 ha with the Krueng Baro river water source. At the last few years, the Baro Kanan Irrigation Area experience limitations in the availability of water. The current problems on the Baro Kanan Irrigation Area are the reduced irrigation water discharge get to agricultural land. Performance evaluation of irrigation network is intended to get an overview of the current conditions. The purpose of the study: 1) Knowing the discharge of water availability and the discharge of water requirements each month in review of the factor K (water balance); 2) Knowing the condition of the irrigation network on the Baro Kanan irrigation systems; 3) Assessment irrigation network performance based on the Regulation of the Minister of Public Works and Public Housing Numbers 12/PRT/M/ 2015. The research method in the form of a survey and documentation for the assessment of irrigation system includes physical infrastructure, cropping productivity, OP supporting facilities, OP implementing personnel organizations, documentation, and institutional condition P3A. From the results of the study obtained the level of water adequacy (factor K) on the Baro Kanan irrigation network of 67%, the condition of the physical infrastructure of 73,7%, cropping productivity of 69,8%, OP supporting facilities of 88,4%, OP implementing personnel organizations 79,7%, documentation 62,8%, and institutional conditions P3A 12%. The performance of the Baro Kanan irrigation network in the category performance of less and need attention with a performance percentage of 67,62%.